MONITORING KELEMBABAN TANAH PADA PENYIRAM TANAMAN OTOMATIS - Nurdiana, Nita; Perawati, Perawati (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2021)
Planting, which is one of the people's hobbies, requires a certain amount of time and scheduling in watering it. Manual watering is sometimes less efficient due to limited time, weather and soil conditions. Soil moisture is an important factor in plant growth. Lack of moisture can cause plants to wilt. Excess moisture can reduce the volume of roots that function to jam. We need a tool that can help watering plants automatically by monitoring soil moisture. In this study, the design of this tool was carried out using the Arduino uno, a soil temperature and humidity sensor. In addition, this tool is also equipped with a DC submersible pump that will stop pumping air to water the plants when the soil moisture limit has been met. Based on the results of the tests that have been carried out, the sensor for moist soil conditions at the time of the assessment value shows a value of 29.94%, the voltage is 2.57 volts, while in wet soil conditions it is indicated by an assessment value of 68.86% with a voltage of 1.094 volts. In general, this tool works in accordance with the design that has been done, namely the relay works to activate the pump to pour water when the sensor detects dry soil conditions and the relay will stop the pump when the soil moisture condition is detected wet by the sensor.